DEVELOPING COMMUNICATION AND PROBLEM SOLVING IN ELEMENTARY SCHOOL MATHEMATICS LEARNING THROUGH PROJECT-BASED LEARNING - Marisa, Riandi; Firmansyah, Juli; Santi, Yulia; Fazilla, Sarah; Anisaturrahmi, Anisaturrahmi (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
The low levels of mathematical communication and problem-solving skills among elementary school students in Indonesia are a serious concern, as reflected in the 2019 TIMSS scores, which fell below the international average (397 out of 487), and the PISA report, which indicates that Indonesian students’ higher-order thinking skills still lag behind those of other Southeast Asian countries. The dominance of conventional, teacher-centered teaching methods is considered one of the main factors hindering the development of these two 21st-century competencies. This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model as an alternative instructional strategy for developing elementary students’ communication and problem-solving skills in mathematics. The study employed a quasi-experimental method with a pre-test and post-test control group design, involving 60 fifth-grade students from two elementary schools in South Jakarta. Data were collected through problem-solving ability tests, mathematical communication assessment rubrics, and learning observation sheets. The results showed that students who learned using PjBL demonstrated significant improvements in problem-solving skills (t = 4.523, p < 0.001, Cohen’s d = 1.12) and mathematical communication (t = 3.876, p < 0.001, Cohen’s d = 0.95) compared to the control group using conventional learning methods. The improvement in the experimental group reached 41% for problem-solving and 44% for mathematical communication, while the control group improved by only 16% and 15%, respectively. These findings indicate that PjBL proved effective in the context of this study and demonstrate its potential for continued use as a learning strategy to develop 21st-century skills in mathematics education at the elementary school level. Keywords: Project-Based Learning, Mathematical Communication, Problem Solving, Elementary School Mathematics Learning, 21st Century Skills